Protein kinase A mediates novel serine-584 phosphorylation of HDAC4 - Doddi, Shanmukha K.; Kummari, Githavani; M.V., Jagannadham; Kalle, Arunasree M. (Biochemistry and cell biology, 2019)
Given the well-established diversified signaling pathways for histone deacetylase 4 (HDAC4) and the regulation of HDAC4 by several post-translational modifications (PTMs), including phosphorylation, sumoylation, and ubiquitination, an unbiased and detailed analysis of HDAC4 PTMs is needed. In this study, we used matrix-assisted laser desorption/ionization time of flight (MALDI-TOF/TOF) to describe phosphorylation at serine 584 (Ser584) along with already-known dual phosphorylation at serines 265 and 266 (Ser265/266), that together regulate HDAC4 activity. Overexpression of site-specific HDAC4 mutants (S584A, S265/266A) in HEK 293T cells, followed by HDAC activity assays, revealed the mutants to be less active than the wild-type protein. In vitro kinase assays have established that Ser584 and Ser265/266 are phosphorylated by protein kinase A (PKA). Luciferase assays driven by the myocyte enhancer factor 2 (MEF2) promoter and real-time PCR analysis of the MEF2 target genes show that the S584A and S265/266A mutants are less repressive than the wild-type. Furthermore, treatment with PKA activators such as 8-Bromo-cAMP and forskolin, and silencing either by shRNA or its inhibitor H-89 in a mouse myoblast cell line (C2C12) and in a non-muscle human cell line (K562), confirmed in vivo phosphorylation of HDAC4 in C2C12 but not in K562 cells, indicating the specific functional significance of HDAC4 phosphorylation in muscle cells. Thus, we identified PKA-induced Ser584 phosphorylation of HDAC4 as a yet unknown regulatory mechanism of the HDAC4–MEF2 axis.